The Potential Anti-inflammatory Effect of Spirulina Platensis on an in Vitro Model of Celiac Disease - Jahani-Sherafat, Somayeh; Alipour, Samira; Olamafar, Ensiyeh; Jahdkaran, Mahtab; Zamanian Azodi, Mona; Khodadoost, Mahmood; Rostami-Nejad, Mohammad (International Journal of Medical Toxicology and Forensic Medicine, 2023)
Background: Celiac disease (CD) is a prevalent autoimmune enteropathy triggered by the ingestion of gluten. The management of CD involves adhering to a gluten-free diet (GFD). Recent studies have been actively exploring potential supplementary or alternative therapies for individuals with CD. The primary objective of the present study was to assess the effectiveness of Spirulina platensis in regulating the intestinal barrier-related gene expression and alleviating inflammation and oxidative stress associated with CD in PT-gliadin-triggered Caco-2 cells. Methods: S. platensis extracts and a pepsin/trypsin (PT) digest of gliadin were prepared and exposed to the human colon carcinoma Caco-2 cell line. Cell viability was assessed. Total RNA was extracted from Caco-2 cells and cDNA synthesis was performed. A quantitative real-time polymerase chain reaction (qRT-PCR) assay was conducted to evaluate the mRNA levels of interleukin (IL)-6, transforming growth factor beta (TGF-β), COX-2, nuclear factor kappa B (NF-κB), ZO-1, and occludin. Results: Treating Caco-2 cells with S. platensis alone (P=0.01 for both) or in combination with PT-gliadin (P=0.004 and P=0.02, respectively) resulted in decreased IL-6 expression and increased occludin mRNA expression. Additionally, S. platensis extract enhanced Zo-1 mRNA levels (P=0.002) and reduced NF-κB mRNA expression (P=0.02). The combination of gliadin and S. platensis led to decreased mRNA expression of COX-2 (P=0.03) and NF-κB (P=0.04). No significant differences were observed in TGF-β mRNA expression between the studied groups (P>0.05). Conclusion: Additional investigation is needed to examine the influence of interactions between S. platensis and gliadin regarding the comprehensive response of CD to gliadin, encompassing the activation of gluten-sensitive immune cells.